2013
DOI: 10.1007/s10096-013-1892-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and antibiotic susceptibility of genital mycoplasmas in sexually active individuals in Hungary

Abstract: The aim of this study was to examine the incidence and antibiotic sensitivity of Ureaplasma urealyticum and Mycoplasma hominis strains cultured from the genital discharges of sexually active individuals who attended our STD outpatient service. Samples were taken with universal swab (Biolab®, Budapest, Hungary) into the Urea-Myco DUO kit (Bio-Rad®, Budapest, Hungary) and incubated in ambient air for 48 h at 37 °C. The determination of antibiotic sensitivity was performed in U9 and arginin broth using the SIR My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…Other two macrolides that were studied-azithromycin and erythromycin -were only moderately effective [32]. Resistance to erythromycin has been reported additionally by Ponyai et al [31] and Krausse et al [33] who determined that the resistance of ureaplasmas to erythromycin is 81% and 21%, respectively. Pignanelly et al [5] studied M. hominis and found that the isolates were sensitive to tetracycline and doxycycline but resistant to fluoroquinolones and macrolides except jocamycin.…”
Section: General Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Other two macrolides that were studied-azithromycin and erythromycin -were only moderately effective [32]. Resistance to erythromycin has been reported additionally by Ponyai et al [31] and Krausse et al [33] who determined that the resistance of ureaplasmas to erythromycin is 81% and 21%, respectively. Pignanelly et al [5] studied M. hominis and found that the isolates were sensitive to tetracycline and doxycycline but resistant to fluoroquinolones and macrolides except jocamycin.…”
Section: General Treatmentmentioning
confidence: 95%
“…Additionally, ureaplasma species have natural resistance to lincosamides (e.g. clindamycin) and M. hominis possesses inherent resistance to macrolides, except josamycin [31].…”
Section: General Treatmentmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Only 10 (58.8%) of these focused their attention on antimicrobial susceptibility. [3][4][5][6][7][8][9][10]13,15] Moreover, 9 (52.9%) articles studied female patients, [2][3][4][5][6]9,11,15,18] 4 (23.5%) male, [7,14,16,17] and 4 (23.5%) both; [8,10,12,13] the populations showed genital disorder in 15 (88.2%) cases. [2,[4][5][6][7][8][9][10]…”
Section: In Vitromentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10]13,15] Moreover, 9 (52.9%) articles studied female patients, [2][3][4][5][6]9,11,15,18] 4 (23.5%) male, [7,14,16,17] and 4 (23.5%) both; [8,10,12,13] the populations showed genital disorder in 15 (88.2%) cases. [2,[4][5][6][7][8][9][10][11][12][13][14][15][16]18] In these works, the prevalence of M. hominis ranged from 0.5% to 39.7% (male 0.5-28.3% and female 0.9-39.7%). [2][3][4][5][6][7][8][9][10]…”
Section: In Vitromentioning
confidence: 99%
See 1 more Smart Citation